REKONTRUKSI PEMIKIRAN ISLAM MODERAT: Studi Komparatif Antara Yudian Wahyudi dan Fazlur Rahman Tentang Islam Kontekstual - Septi Putri, Wulan; Raka Chiwi, Rayyan; Sadari, Sadari (Moderation | Journal of Islamic Studies Review, 2026)
The thoughts of Yudian and Rahman are crucial in the development and enrichment of moderate Islamic discourse in the contemporary era. In an increasingly complex and dynamic global context, moderate Islamic discourse is crucial for bridging the gap between religious tradition and the demands of modernity, as well as between religious teachings and pluralistic social life. The thoughts of these two figures offer a strong foundation and a relevant perspective to address the various challenges facing Muslims today. One of the most relevant aspects of their thinking is how moderate Islam is positioned as a balanced middle ground between rigid conservatism and excessively liberalism. Both thinkers emphasize the importance of maintaining fundamental Islamic values without precluding the possibility of renewal and adaptation in accordance with current developments. In a situation where the polarization of religious thought is increasing and various forms of extremism are emerging that have the potential to threaten social harmony, the thoughts of Yudian and Rahman provide a moderate, inclusive, and constructive alternative. Rahman's thought, with its hermeneutic approach and focus on the maqasid sharia, provides a strong theoretical framework for understanding Islamic teachings in depth and context. This approach is highly relevant to addressing contemporary global and multidimensional issues, such as human rights, religious pluralism, and advances in science and technology. In a global context, Rahman's thinking encourages Muslims to foster dynamic dialogue and interpretation to ensure their relevance and positive contribution to modern civilization. This approach sees Islam not as a rigid and exclusive religion, but as a religion of mercy for all creation, upholding the values of humanity and justice. Furthermore, Yudian's practical and contextual thinking is instrumental in creating a moderate Islamic framework that is applicable to Indonesian society, which comprises diverse ethnicities, religions, and cultures. Addressing socio-political challenges such as intolerance, radicalism, and intergroup conflict, Yudian's ideas on interfaith dialogue and pluralism provide effective solutions for building harmony and tolerance. With Islam as a moderate and inclusive social force, Yudian's thinking contributes to maintaining social stability and strengthening democracy in Indonesia. Both thinkers emphasize the importance of education and critical thinking in fostering awareness among Muslims about the values of moderation. Education is the primary medium for transmitting the values of tolerance, justice, and openness to diversity. With education based on moderate Islamic thought, the younger generation will be able to understand religious teachings more holistically, be open to change, and avoid harmful extremist attitudes.